“DIPLOMASI BERSIH” DALAM PERSPEKTIF ISLAM - Tulus Warsito; . Surwandono (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2015)
In a general sense, diplomacy is all that is done in managing the relations between nation-states. While the core action substantially diplomacy is negotiation, i.e. how each party attempting to solve all sorts of disputes emerging between the two countries or more. Thus “Clean Diplomacy” in this sense can be meant as a concept or action accountable negotiations, transparent and fair for all parties involved in the dispute between countries. This paper is written for understanding more about nor value concept “Clean Diplomacy” from the perspective of Islamic thought. Analyze more deeply on how to enact Islamic values “clean” diplomacy in negotiations.Keywords: Diplomacy, negotiation, an Islamic perspective